Pidana Pengawasan sebagai Pidana Pokok dalam Perspektif KUHP Nasional - Desak Kadek Era Dewi Susanti; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This research aims to examine the provisions and status of probation as a principal punishment in the National Criminal Code, as well as its relevance to achieving the objectives of reforming the penal system in Indonesia. The research design employed is normative legal research using a legislative and conceptual approach. The data utilized consists of secondary data obtained through a literature review, analyzed using qualitative descriptive techniques. The results of the research show that probation under Law No. 1 of 2023 on the Criminal Code has been established as one of the principal penalties that can be directly imposed by a judge, thus no longer merely a component of conditional sentences as in the old Criminal Code. This regulation reflects a paradigm shift in sentencing from a retributive approach toward a rehabilitative and restorative approach by providing offenders with the opportunity to remain within the community under supervision. However, its implementation still faces challenges, including the absence of comprehensive technical regulations, potential conflicts of norms, and institutional limitations in carrying out supervision. Therefore, supervised probation holds significant relevance as a more humane sentencing alternative, although it requires strengthened regulations and a supervision system to ensure its effective and consistent application.